The diagnostic utility of fibrosis-4 or nonalcoholic fatty liver disease fibrosis score combined with liver stiffness measurement by fibroscan in assessment of advanced liver fibrosis: a biopsy-proven nonalcoholic fatty liver disease study. Issue 5 (May 2020) - Jafarov, Fuad; Kaya, Eda; Bakir, Alev; Eren, Fatih; Yilmaz, Yusuf
Abstract : Background/aim: The clinical guidelines recommend the use of nonalcoholic fatty liver disease fibrosis score and fibrosis-4 score for estimating the advanced liver fibrosis in nonalcoholic fatty liver disease. However, these scores are used confidently in eliminating advanced fibrosis, rather than detecting it. Therefore, paired combination with liver stiffness measurement by transient elastography is recommended. In this study, we aimed to validate this combined algorithm in our study population. Methods: A total of 139 consecutive biopsy-proven nonalcoholic fatty liver disease patients were enrolled in the study. We calculated the noninvasive scores and performed liver stiffness measurement examination for each patient. Results: The optimal cutoff of liver stiffness measurement for advanced fibrosis was 11.0 kPa (area under curve: 0.856) with a sensitivity of 84% and a specificity of 78%. Using the fibrosis-4 score (< 1.45 for low risk of advanced fibrosis and > 3.25 for high risk of advanced fibrosis) in combination with the liver stiffness measurement cutoffs revealed the best diagnostic performance (< 8.8 kPa for low risk of advanced fibrosis and > 10.9 kPa for high risk of advanced fibrosis). This paired combination had the positive predictive value of 0.735 at a sensitivity of 89% and the negative predictive value of 0.932 at a specificity of 82%. Conclusion: A paired combination of the fibrosis-4 score and liver stiffness measurement (< 8.8 kPa for exclusion of advanced fibrosis and > 10.9 kPa for inclusion of advanced fibrosis) is able to diagnose the patients with advanced fibrosis with the highest diagnostic accuracy.